Tautinės tapatybės suvokimo raida misterijose - Martišiūtė, Aušra (Literatūra, 2015)
The article deals with the unique genre of Lithuanian dramaturgy – mystery plays, the performance of which under the open sky became a significant phenomenon in the cultural life of independent Lithuania. The article introduces the genesis of the genre of mystery plays and focuses on the problems of national identity in the works of the end of the 19th century as well as outstanding pieces of the genre of mystery plays, written in the 1st and 3rd decades of the 20th century (Vydunas Shadows of the Ancestors, 1900–1908; J. A. Herbaciauskas The Hymn of Lithuania’s Ruins, 1907; V. Kreve Along the Paths of Destiny, 1921–1929, V. Mykolaitis-Putinas Uncrowned Virgin of the Fire, 1927). The content of national identity in mystery plays is made up by giving a changing prominence to the aspects of the Lithuanian language, Lithuanian history, and national culture. The search for national identity at the junction of the centuries raises the problem of historical memory, as well as the significance of cultural memory and aesthetical and philosophical reflection is actualized in the 3rd decade.